TNF‐Stimulated Gene-6 Is a Key Regulator in Switching Stemness and Biological Properties of Mesenchymal Stem Cells. (14th May 2019) - Romano, Barbara; Elangovan, Sudharshan; Erreni, Marco; Sala, Emanuela; Petti, Luciana; Kunderfranco, Paolo; Massimino, Luca; Restelli, Silvia; Sinha, Shruti; Lucchetti, Donatella; Anselmo, Achille; Colombo, Federico Simone; et al.
Abstract: Mesenchymal stem cells (MSCs) are well established to have promising therapeutic properties. TNF-stimulated gene-6 (TSG-6), a potent tissue-protective and anti-inflammatory factor, has been demonstrated to be responsible for a significant part of the tissue-protecting properties mediated by MSCs. Nevertheless, current knowledge about the biological function of TSG-6 in MSCs is limited. Here, we demonstrated that TSG-6 is a crucial factor that influences many functional properties of MSCs. The transcriptomic sequencing analysis of wild-type (WT) and TSG-6 −/− -MSCs shows that the loss of TSG-6 expression leads to the perturbation of several transcription factors, cytokines, and other key biological pathways. TSG-6 −/− -MSCs appeared morphologically different with dissimilar cytoskeleton organization, significantly reduced size of extracellular vesicles, decreased cell proliferative rate, and loss of differentiation abilities compared with the WT cells. These cellular effects may be due to TSG-6-mediated changes in the extracellular matrix (ECM) environment. The supplementation of ECM with exogenous TSG-6, in fact, rescued cell proliferation and changes in morphology. Importantly, TSG-6-deficient MSCs displayed an increased capacity to release interleukin-6 conferring pro-inflammatory and pro-tumorigenic properties to the MSCs. Overall, our data provide strong evidence that TSG-6 is crucial for the maintenance of stemness and other biological properties of murine MSCs. : Abstract : Loss of TNF-stimulated gene-6 (TSG-6) in murine mesenchymal stem cells drives changes in cell morphology and actin-cytoskeleton organization that ultimately impact cell proliferation and differentiation capacities of mesenchymal stem cells. TSG-6 regulates the expression of transcription factors involved in several mesenchymal stem cell cellular processes, crucial for the maintenance of stemness and key biological properties. Its loss led to the abrogation of immunomodulatory properties conferring to mesenchymal stem cells, a pro-tumorigenic phenotype by an increased capacity to release interleukin-6.